Analysis of the Schedule of Budget Implementation, Organizational Commitment, and Bureaucratic Reforms on Budget Absorption in the North Tapanuli Regency Government - Bonifasius H. Tambunan (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The purpose of this study was to analyze the effect of budget execution, bureaucratic reform, and organizational commitment to budget absorption with the quality of human resources as a moderating variable in the regional government organizations of North Tapanuli Regency. The population used was all regional apparatus organizations of the North Tapanuli Regency Government, totaling 45 (forty five) regional apparatus organizations. The sampling technique in this study was carried out by the census method or saturated sample, where all members of the population were sampled. Furthermore, 2 (two) questionnaires will be given to each regional apparatus organization which will be filled in by the Financial Administration Officer and the Expenditure Treasurer of the regional apparatus organization. So that the total sample to be used is 90 respondents. The type of data used in this research is primary data. The analytical method used is multiple linear regression analysis and interaction test. The results of this study indicate that the quality of the budget execution checklist, budget reform has a positive effect on budget absorption in the regional apparatus of the North Tapanuli Regency Government. Organizational commitment has no effect on budget absorption in the regional apparatus of the North Tapanuli Regency Government. The quality of human resources cannot moderate the relationship between the quality of the budget implementation checklist, budget reform, and organizational commitment and budget absorption in the regional apparatus of the North Tapanuli Regency Government.